Bioprospecting of fungi isolated from the gut of Amazonian of the order Coleoptera with anti-candida sp activity. (Research, Society and Development, 2023)
With an unbridled exploitation of natural resources, much of the world's biodiversity has been decreasing over the years. With all the Amazonian wealth, Brazil is given the advantage in the search for national development, through the proper exploitation of these resources, minimizing damage to the environment. In this sense, Bioprospection emerges as a tool for Sustainable Development, which can be understood as the systematic search for organisms, genes, enzymes, compounds, processes and parts from living beings, which have economic potential and eventually lead to the development of a product. Many fungi live in symbiotic or commensal associations in beetle intestines and these fungi have an as yet unknown ability to produce as yet unknown substances. In view of these relationships, this research aims to carry out a Bioprospection of filamentous fungi extracted from the gut of Amazon beetles. The results are promising when highlighting the antifungal activity against strains of Candida sp species whit the studied extract fractions from Fusarium Incarnatum – equisetti species.